Investigating the Relevance of ESP Materials in Indonesian Vocational Schools: The Voice of Pharmacy Students - Terra Dewanto, Ardan Cahya; Setyaningsih, Endang; Putra, Kristian Adi (VELES Voices of English Language Education Society, 2024)
Previous English for Specific Purposes (ESP) studies have focused on examining relevant ELT learning materials within universities, with less attention given to vocational senior high schools. This study examined the relevance of ESP materials in an Indonesian vocational high school of pharmacy, as perceived by students. This narrative research in Central Java involved 30 twelfth-grade participants who shared their perspectives on genres, learning activities, and assessment through narrative frames and follow-up interviews. Thematic analysis revealed that many students found the ESP learning materials irrelevant to their specific needs within the pharmacy field. Discussions highlighted the students' desire for enhanced communicative competence to serve patients better, explain medicine usage, and comprehend medical prescriptions. The study suggests implementing communicative language teaching techniques to improve students' communicative competence and use of specialized vocabulary. Despite challenges with pronunciation and grammar, students demonstrated overall comprehension of the materials. In sum, this study offers valuable insights for curriculum designers and teachers in vocational senior high schools seeking to create more effective ESP learning materials.